The effect of self-efficacy and achievement motivation on agriculture student learning outcomes - Eka Aprilianty (Jurnal Taman Vokasi, 2018)
This is descriptive research with aims to determine the effect of self-efficacy, achievement motivation, and self-efficacy and achievement motivation together on student learning outcomes in the Agriculture Sector of SMK Muhammadiyah Pangkalan Bun in the academic year 2017/2018. It had used the survey method with a population of 81 people and the sample used was 65 students. Data analysis techniques were using descriptive statistics and inference statistics, and hypothesis testing using multiple regression analysis with SPSS 16. Obtained results were self-efficacy has a positive and significant effect on student learning outcomes with a contribution of 65.3%. Achievement motivation has a positive and significant effect on student learning outcomes with a contribution of 26%. Self-efficacy and achievement motivation have a positive and significant effect together on student learning outcomes. The variation in the score of learning outcomes about 68.10% could be explained by a combination of these two variables. While 31.90% is influenced by other variables were not examined in this study.